Disruptive product innovations : a new definition and seven theses - Frank Koppenhagen and Christoph Hubert Wecht and Tobias Held (American Journal of Mechanical and Industrial Engineering, 2024)
The importance of disruptive product innovations is undisputed. However, the understanding of what constitutes a disruptive innovation varies widely in academic discourse. Therefore, this paper begins with a new definition of disruptive product innovation based on the design of the product innovation and its subsequent adoption by competitors. It then presents the results of an ongoing research project that uses a qualitative case study approach to analyze product innovations from the last fifty years that meet this definition. Both the design and the development process of these product innovations have been examined in detail. In particular, the effective principles and structures, geometric layouts and operating concepts used in the product innovations were analyzed, as were the differences to previous products. In addition, changes in the social and technological environment that led to the innovations were examined, as well as the role of new enabling technologies, in particular new materials and production processes. The common patterns across cases identified through the analysis were condensed into seven theses, which are presented in this article, each of them illustrated by using the example of the first iPhone. Said theses reflect the central research findings on (1) "Key usability contradictions as starting points", (2) "User-centeredness", (3) "Co-evolution of problem and solution space", (4) "Technical fixations that create cognitive gravitation", (5) "Facilitation through new technologies and reciprocal enablers", (6) "Higher degree of ideality" and (7) "Shifting tasks in the overarching human-product interaction system to the product". Finally, starting points for further research are formulated.
Keywords: Disruptive Innovationen; Innovation; Product Design; Product Innovation; iPhone; Design Thinking